Prototipe Pengendalian Kualitas Udara Indoor Menggunakan Mikrokontroler dengan Sensor MQ135, DHT-22 dan Filter HEPA - Gita Pati Humairoh; Rama Dani Eka Putra (Fakultas Teknik, 2022)
Indoor air pollution is a very serious health issue in comparison with outdoor air conditions. The current pandemic of COVID-19 causes people to remain indoors at all times. It is unimaginable that during this pandemic a smog-related disaster could occurs that could aggravate human respiratory diseases, thus requires additional air quality monitoring which can filter clean air into the room. The purpose of this study is to produce a prototype of air quality control that can provide a good air circulation system and hold the temperature and humidity in the room. This research was conducted with an Arduino Uno microcontroller and an MQ-135 gas sensor to detect CO2 gas and a DHT-22 sensor for measuring room temperature and humidity by comparing the results of using a HEPA filter. The research results of the prototype make it possible to generate the room temperature using a HEPA filter and air humidifier whose average is 27.7°C. Another parameter that is performed is the CO2 measurement, it is found that the average CO2 in the test using a HEPA filter and an air humidifier is 496 PPM.